Endogenous Money Supply and Money Demand - Choi, Woon (IMF Working Papers; Working Paper, 2000)
This paper explores the behavior of money demand by explicitly accounting for the money supply endogeneity arising from endogenous monetary policy and financial innovations. Our theoretical analysis indicates that money supply factors matter in the money demand function when the money supply partially responds to money demand. Our empirical results with U.S. data provide strong evidence for the relevance of the policy stance to the demand for MI under a regime in which monetary policy is substantially endogenous. Specifically, we find that tighter monetary policy has substantial positive impacts on money demand under the recent Federal funds rate targeting.